A conceptual modelling framework for assessment multiple soil degradation: A case study in the region of Šumadija and Western Serbia. (April 2023) - Perović, Veljko; Čakmak, Dragan; Srbinović, Olivera Stajković; Mrvić, Vesna; Simić, Snežana Belanović; Matić, Marija; Pavlović, Dragana; Jaramaz, Darko; Mitrović, Miroslava; Pavlović, Pavle
Graphical abstract: Highlights: Geospatial analysis of multiple soil degradation processes in Serbia was conducted. Soil degradation is mainly affected by physical degradation with a 55% impact. The impact of chemical degradation is estimated at 16%. 59% of the region is currently degraded through synergistic effects. Abstract: Soil degradation is a global problem and researchers are facing the challenge of assessing the scale, trends, and consequences of contributing processes. With this in mind, this study implemented the new concept of multiple soil degradation indices (MSDI) for the first time in the region of Šumadija and Western Serbia (SWS). This concept enables the simultaneous integration of several environmental components that can act separately or synergistically and offers concrete answers and information on the state and distribution of physical (PSDI), chemical (CSDI) and biological (BSDI) soil degradation. Using several different geospatial-modelled approaches, results indicated that physical degradation was the greatest contributor to soil degradation in the SWS region with an impact of 55%, followed by chemical degradation at 16%, while biological degradation only had a 6% impact. The dominant indicator of physical degradation was the vegetation cover management factor with an impact of approximately 58%, while for chemical degradation it was soil organic matter, with a relative impact of almost 49%. Total microflora and total number of fungi were the most significant biological indicators with an average impact of approximately 43%. In addition, this study indicated that about 59% of the region is currently degraded, with about 44% of it classified as moderately degraded. The results of this study offer new insights into the geospatial dynamics of interactive degradation processes in Serbia and can form the basis for strengthening scientific, expert, and political support when implementing international and national policies concerned with protecting soil from degradation.